Morphological, Pathogenic, Genetic And Molecular Variabilities Of Fusarium Spp., The Pathogens Of Asparagus Crown And Root Rot In Malaysia And Brunei Darussalam - Al-Amodi, Mohamed Othman Saeed (2006)
Asparagus (Asparagus officinalis) is becoming more important in South East Asia (SEA) and quickly becoming a preferred vegetable. All varieties planted throughout SEA have been and now are still facing the most destructive disease i.e. asparagus crown and root rot. The main aim of the thesis was to collect and isolate Fusarium spp. from asparagus plants showing crown and root rot symptoms and their soils in Malaysia and Brunei Darussalam. The other objectives were to evaluate pathogenicity and genetic diversity within the Fusarium spp. and their variability using peR-based RAPD. A total of 110 isolates comprising five species of Fusarium have been isolated from six sampling areas in Malaysia and one in Brunei Darussalam. The five species identified were F. proliferatum, F. oxysporum, F. solani, F. semitectum and F. /ongipes, based on morphological characteristics. F. proliteretum and F. oxysporum represented the highest percentage (830/0). Pathogenicity tests of F. proiiteretum and F. oxysporum isolates by inoculating healthy asparagus seedlings var. UC157 in the greenhouse confirmed that all isolates tested were pathogenic. The typical symptoms were initially observed as yellowing of leaves and branches. Infected plants were stunted with reddishbrown discoloration and shrivelled roots. Sliced crowns and stems clearly showed reddish-brown discolorations of the infected tissues. Heavily infected plants collapsed and died.